Epidemiology and Clinical Characteristics of Patients with Hepatocellular Carcinoma in North-East of Iran - Homaei Shandiz, Fatemeh; Aledavood, Seyed Amir; Delghandi, Rozita; Fani, Mona; Gholoobi, Aida; Yahyazadeh Mashhadi, Seyed Muhammad; Abdoli, Mohsen; Gouklani, Hamed; Geraily, Sina; Meshkat, Zahra (Archives of Medical Laboratory Sciences, 2020)
Background: Hepatocellular carcinoma (HCC), the most common type of primary liver cancer, is a life-threatening disease worldwide. The aim of this study was to investigate the epidemiology and clinical features of HCC patients who referred to Omid hospital in Mashhad, northeast of Iran. Materials and Methods: In this cross sectional retrospective study, we reviewed the medical records of patients who referred to Omid hospital – a cancer research center– in Mashhad during 1991 to 2012. Medical records of 29 patients with primary liver cancer proven with biopsy, CT scan or MRI were analyzed in this study. Results: Of 25 eligible cases, 68% were men and the rest were women. The majority of HCC patients were in the 60-69 age group. Also, 44% of patients were found to be hepatitis B virus surface antigen (HBsAg) positive. Conclusion: The age distribution and male preponderance of HCC patients observed in the present study in line with other conducted studies in Iran and other countries. Since this is a retrospective study, a comprehensive study with a larger sample size in a case-control study is needed to establish other HCC-related factors in our province.